A velva nutmeg Karakteristik Fisikokimia dan Sensori Velva Buah Pala (Myristica fragrans Hout) dengan Penmbahan CMC (Carboxy Methyl Cellulose): Indonesia - Najah, Hamliyatun; Pertiwi, Sri Rejeki Retna; Kusumaningrum, Intan (JURNAL AGROINDUSTRI HALAL, 2021)
Nutmeg is a type of fruit from medicinal plants found in Bogor, which has a high antioxidant content. The purpose of this study was to formulate velva made from nutmeg as a diversification in food processing which was evaluated by analyzing the physical, chemical and sensory properties of selected velva. In this study, nine velva formulations of nutmeg with different concentrations of water were made, Carboxy Methyl Cellulose (CMC), and nutmeg puree. The results showed that the selected velva of nutmeg based on sensory characteristics was velva made with a formula of 100 g of nutmeg, 60 ml of water, and 0.6% CMC. The selected velva of nutmeg has the characteristics of brownish yellow, softness, neutral texture, the strength of the neutral aroma, the taste is slightly harsh, and the overall taste is quite favorable. Physical properties analysis showed that the velva of selected nutmeg had an overrun of 5.87%, yield power of 227.50 seconds, and total dissolved solids of 14.10% Brix. The chemical content of selected velva nutmeg produces 83.05% moisture content, 0.11% ash content, 5.23% protein content, 3.43% fat content, 8.15% carbohydrate content, 76.59 ppm antioxidant content.